ESTABLISHMENT AND PRACTICE OF UNDERGRADUATE EDUCATION SYSTEM FOR MARINE SURVEYING AND MAPPING IN THE NEW STAGE - F. Yang; S. Liu; C. Qin; K. Zhang; X. Cui; J. Sun (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2023)
In 2012, China announced its national strategy of building marine power. With the booming of marine development activity, the demand for marine surveying and mapping has increased sharply. However, education for the discipline lagged far behind the growth in demand. For a long time, education in the marine surveying and mapping discipline has faced two problems. First, the education content is mainly for military purposes, and there is little content about civilian use. Second, the education content is outdated and is far from the frontier science and engineering practice. To address these problems, Shandong University of Science and Technology has been working on the education reformation of the marine surveying and mapping discipline for more than a decade. By cooperating with our education partners from the military college, the universities, and the enterprises in maritime industries, we deeply analyzed the booming need in the marine survey and mapping field, and clarified the connotation and characteristics of the discipline in the new era. The discipline roots in the geodesy discipline, but is also deeply connected with oceanography, electromagnetics, and underwater acoustic. Moreover, it serves the national marine strategy and coastal economic development. Thus, it is an interdisciplinary emphasizing practicality and innovation. To this end, under the framework of military-civilian cooperation and industry-education integration, we establish an education alliance with participants from marine institutes, universities, industries, and users. Based on the close collaboration within the alliance, we built a new education model for undergraduate students in the marine surveying and mapping discipline. During the last decade, more than 3000 undergraduate students have been educated to fill the needs of employers relative to the marine economy. Moreover, more than 500 students obtained the qualifications as international hydrographic surveyors and cartographers, and they make worthwhile contributions to the national marine strategy and marine economic development.